The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.neuropsychologia.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of helplessness increase ERN amplitudes in healthyindividuals

Abstract: Experiencing feelings of helplessness has repeatedly been reported to contribute to depressive symptoms and negative affect. In turn, depression and negative affective states are associated, among others, with impairments in performance monitoring. Thus, the question arises whether performance monitoring is also affected by feelings of helplessness.To this end, after the induction of feelings of helplessness via an unsolvable reasoning task, 37 participants (20 females) performed a modified version of a Flanke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 74 publications
4
23
2
Order By: Relevance
“…The result that participants with low alexithymia showed enhanced error-monitoring activity with the emotional task set is in accordance with previous studies, which found increased Ne/ERN amplitudes when the activity of the affective system was increased by presenting task-irrelevant affective information (e.g., Pfabigan et al, 2013;Wiswede, Münte, Goschke, & Rüsseler, 2009). Note that the affective content of the task set enhanced exclusively the Ne/ERN on error trials, but did not affect the ERP in the Ne/ERN time window on correct trials.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result that participants with low alexithymia showed enhanced error-monitoring activity with the emotional task set is in accordance with previous studies, which found increased Ne/ERN amplitudes when the activity of the affective system was increased by presenting task-irrelevant affective information (e.g., Pfabigan et al, 2013;Wiswede, Münte, Goschke, & Rüsseler, 2009). Note that the affective content of the task set enhanced exclusively the Ne/ERN on error trials, but did not affect the ERP in the Ne/ERN time window on correct trials.…”
Section: Discussionsupporting
confidence: 92%
“…However, errors themselves are aversive (e.g., Hajcak & Foti, 2008;Riesel, Weinberg, Moran, & Hajcak, 2013; but see Moser, Moran, Schroder, Donnellan, & Yeung, 2014), and not surprisingly, the Ne/ERN is modulated by motivational and affective variables. For instance, the component is increased following the induction of negative affect (Pfabigan et al, 2013;Wiswede, Münte, Goschke, & Rüsseler, 2009;, and in individuals with high negative affectivity (Hajcak, McDonald, & Simons, 2004;Luu, Collins, & Tucker, 2000) or anxiety (Hajcak, McDonald, & Simons, 2003;Weinberg, Olvet, & Hajcak, 2010;see Moser, Moran, Schroder, Donnellan & Yeung, 2013, for a review). Furthermore, the Ne/ERN amplitude is larger, when errors entail more negative consequences (Hajcak, Moser, Yeung, & Simons, 2005;Maier & Steinhauser, 2013), and predicts priming of negative word evaluation by erroneous responses (Aarts, De Houwer, & Pourtois, 2013).…”
Section: Abstract Cognitive Control Emotion Event-related Potentimentioning
confidence: 99%
“…It is possible that there is a difference between a brief and fleeting exposure to meditation state and long-term meditation traits (such as emotional acceptance as measured in the Teper and Inzlicht study). That said, studies tend to indicate improved attention, rather than decreased attention, in those who practice mindfulness meditation (Jha et al, 2007; Tang et al, 2007; Zeidan et al, 2010; Moore et al, 2012) and there are several studies that do not show affective trait-related changes in Pe amplitude (Clayson et al, 2012; Larson et al, 2013; Pfabigan et al, 2013). Thus, while an interesting finding, future studies need to directly manipulate error salience, error awareness, orienting to errors, and mindfulness meditation in the moment vs. as a more ingrained trait to clarify the Pe and mindfulness relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The use of human participants followed the guidelines of the Helsinki Declaration and was approved by the Research Ethics Committee of China Astronaut Research and Training Center. Only participants with a minimum of 5 error trials which yielded distinct ERN peaks were included in further data analysis [27]. Four participants had to be excluded from further analysis due to data acquisition artifacts (n=2), or due to committing less than 5 errors (n=2).…”
Section: Participantsmentioning
confidence: 99%
“…Data were baseline-corrected from -400 to -200 ms for response-locked epochs before computation of averages for each condition. The minimum number of trials used for ERN (0-120 ms) was not less than 5 [27], and the ERN mean amplitudes were quantified at Fz/Cz/FC1/FC2 sites.…”
Section: Electrophysiological Recording and Processingmentioning
confidence: 99%